Dinamika implementasi program MBKM: preferensi mahasiswa, dukungan institusi, dan tantangan - Ni Kadek Dwi Awidiya; Edy Herianto; Bagdawansyah Alqadri (Journal of Education, Cultural and Politics, 2026)
This study aims to analyze the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy in the Civic Education Study Program, Faculty of Teacher Training and Education, University of Mataram. The research employed a qualitative approach with a case study design. Informants consisted of the head of the study program, lecturers, and students selected through purposive sampling. Data were collected through questionnaires, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that the implementation of the three-semester learning policy outside the study program is carried out through program socialization, administrative services, academic supervision, program monitoring, and credit conversion. The most preferred MBKM activity among students is the student exchange program. Supporting factors include credit conversion systems, collaboration with partners, academic supervision, and student motivation. However, challenges include time management, academic readiness, communication with the study program, and differences in implementation mechanisms across MBKM activities.